MEWUJUDKAN PENGEMBANGAN PARIWISATA BERBASIS MASYARAKAT PADA OBYEK WISATA PANTAI PETITENGET, SEMINYAK, BADUNG, PROVINSI BALI - Romanus Gandur; Gusti Ayu Mahanavami; Wiryawan Suputra Gumi; I Wayan Tantra (Lembaga Penelitian dan Pengabdian Masyarakat (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2023)
The Petitenget Seminyak beach tourist attraction is managed by the local community in order to fully utilize and empower its human resources, where all workers come from the local community. The objectives of this research are 1) To find out the participation of local communities in developing Petitenget Beach tourism in Seminyak Bali, 2) To find out the benefits obtained by local communities in developing Petitenget Beach tourism in Seminyak, Badung Regency, Bali Province. Data collection techniques use observation, interviews, literature study and documentation, while the data analysis techniques used are data reduction analysis, data presentation and drawing conclusions. The research results show that 1) The participation of the local community of Kerobokan Village in the development of Seminyak Petitenget Beach tourism must be maintained and increased from the stages of community participation in decision making, participation in activities, participation in evaluation and participation in utilization of results so that the development process continues to run well and becomes a tourist attraction that attracts many visitors, and 2) Utilizing the development of Petitenget Seminyak beach tourism can provide employment opportunities for the community and increase village income.